Public potato breeding progress for the Nordic Region of Europe: evidence from multisite testing of selected breeding clones and available released cultivars. (31st December 2022) - Reslow, Fredrik; Carlson-Nilsson, Ulrika; Crossa, José; Cuevas, Jaime; Ortiz, Rodomiro
ABSTRACT: The breeding of new cultivars is a powerful approach to increase both the quantity and quality of potato harvest per land unit. The aim of this research was to determine using multi-site testing the progress made by the genetic enhancement of potato in Sweden in the last 1.5 decades by comparing advanced breeding clones (T4 upwards) bred in Sweden (Svensk potatisförädling hereafter) versus available released cultivars in Europe and grown in its Nordic Region. The multi-site testing results show that potato breeding based in Scandinavia offers to the growers of the Nordic Region of Europe cultivars for prevailing farming environments and end-user needs rather than relying, as happens today in the market, on foreign cultivars. These cultivars bred elsewhere are not always very suitable for the challenging Nordic agroecosystems, as shown by the results of the multi-site testing herein. Such an approach on relying on foreign cultivars may be advocated for not funding potato breeding in, and for Fennoscandia by those ignoring the results shown by this research.